2011
DOI: 10.1029/2010je003729
|View full text |Cite
|
Sign up to set email alerts
|

M3 spectral analysis of lunar swirls and the link between optical maturation and surface hydroxyl formation at magnetic anomalies

Abstract: [1] We examined the lunar swirls using data from the Moon Mineralogy Mapper (M 3 ). The improved spectral and spatial resolution of M 3 over previous spectral imaging data facilitates distinction of subtle spectral differences, and provides new information about the nature of these enigmatic features. We characterized spectral features of the swirls, interswirl regions (dark lanes), and surrounding terrain for each of three focus regions: Reiner Gamma, Gerasimovich, and Mare Ingenii. We used Principle Componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 73 publications
8
85
1
Order By: Relevance
“…The Diviner data, therefore, suggest that a layer of fine particulate feldspar-enriched material is not responsible for the lunar swirl albedo anomalies and spectral properties. This interpretation supports visible and near-infrared measurements from the M 3 instrument 15 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The Diviner data, therefore, suggest that a layer of fine particulate feldspar-enriched material is not responsible for the lunar swirl albedo anomalies and spectral properties. This interpretation supports visible and near-infrared measurements from the M 3 instrument 15 .…”
Section: Resultssupporting
confidence: 77%
“…On the other hand, the solar wind standoff mechanism for swirl formation would lead to a slight shift of the CF to shorter wavelengths compared with the surrounding regolith due to a reduction in space weathering, but show no difference in the unique lunar regolith thermophysical properties because impact gardening is otherwise unaffected. These properties are exactly what are observed, and the Diviner observations, in addition to M 3 and Mini-RF 14,15,40 observations and laboratory experiments 42 , strongly support the solar wind standoff hypothesis for lunar swirl formation. Because they are clearly associated with magnetic field anomalies, lunar swirls present an opportunity to study and isolate the effects of solar wind sputtering/implantation and micrometeoroid bombardment processes on optical maturity.…”
Section: Article Nature Communications | Doi: 101038/ncomms7189supporting
confidence: 65%
See 1 more Smart Citation
“…Water transport from polar craters to mid-latitudes (liberated by impact vaporization and sputtering) was found to be plausible but could not account for the relatively large hydroxylation levels observed in the IR (Farrell et al, 2013). Kramer et al (2011) found that the local IR OH absorption feature was reduced (less OH content) in swirl regions associated with magnetic anomalies. The finding suggests that hydroxylation is locally reduced where the B-field also blocks solar wind propagation onto the surface (Kramer et al, 2011;Poppe et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…The radar brightness indicates increased surface and/or near subsurface roughness close to the scale of the radar wavelength (in the case of Mini-RF, centimeter The radar image is displayed as colorized circular polarization ratio over total radar backscatter. An arrow indicates the edge of a newly discovered impact melt flow (Neish et al, 2011;Kramer et al, 2011;Carter et al, 2012). In this figure, north is up.…”
Section: Observationsmentioning
confidence: 93%